Ukraine or Little Russia? Revisiting the Early Nineteenth - Century Debate - Plokhii, S. (Інститут історії України НАН України, 2008)
This paper departs from the existing literature on the «History of the Rus’», at once the most mysterious and the most influential product of Ukrainian Cossack historiography, in two major respects. First, it challenges the dominant historiographic trend that treats the «History» as a manifestation of proto-national and autonomist Ukrainian aspirations. Second, it contributes to the perennial search for the author of the «History» by claiming that the manuscript was written soon after 1800, effectively locating the work in the realm of nineteenth-century historiography. More than anything else, however, this paper takes the debate out of the Procrustean bed into which it was forced by the national narratives of a later era, both Ukrainian and all -Russian. It emphasizes the simple fact that historians have little control over the use of their narratives.